Jellyfish genomes reveal distinct homeobox gene clusters and conservation of small RNA processing - Nong, W; Cao, J; Li, Y; Qu, Z; Sun, J; Swale, T; Yip, HY; Qian, PY; Qiu, J-W; Kwan, HS; Bendena, W; Tobe, S; et al. (Springer Nature, 2020)
The phylum Cnidaria represents a close outgroup to Bilateria and includes familiar animals including sea anemones, corals, hydroids, and jellyfish. Here we report genome sequencing and assembly for true jellyfish Sanderia malayensis and Rhopilema esculentum. The homeobox gene clusters are characterised by interdigitation of Hox, NK, and Hox-like genes revealing an alternate pathway of ANTP class gene dispersal and an intact three gene ParaHox cluster. The mitochondrial genomes are linear but, unlike in Hydra, we do not detect nuclear copies, suggesting that linear plastid genomes are not necessarily prone to integration. Genes for sesquiterpenoid hormone production, typical for arthropods, are also now found in cnidarians. Somatic and germline cells both express piwi-interacting RNAs in jellyfish revealing a conserved cnidarian feature, and evidence for tissue-specific microRNA arm switching as found in Bilateria is detected. Jellyfish genomes reveal a mosaic of conserved and divergent genomic characters evolved from a shared ancestral genetic architecture.